The Evaluation of Violence Perception and Approaches to Women in Law Faculty Students - Gürpınar, Kağan; Pakiş, Işıl; Terece, Cem; Polat, Mehmet Oğuz (The Bulletin of Legal Medicine, 2020)
Objective: It is known that violence against women is an important health problem. The aim of this study is to investigate the awareness, knowledge and attitudes of law faculty students about violence against women and offer solutions to this problem. Materials and Methods: 192 students from Maltepe University Faculty of Law attended the study. Research data were collected by a questionnaire prepared by the researchers. The age range of students who participated in this study is 18-38 and the average age is 21.6. Results: In the study, egalitarian views on social gender roles and equality vary between 70.9% and 90.7% of responses given to the propositions. The rate of students agreeing with the proposition of “In some cases women deserve to be beaten by their partners” is 9.9%. The rate of women who agreed with egalitarian propositions are significantly higher than in men (p<0.005). The awareness of physical, economic and sexual violence is significantly higher in women than men. Gender equal- ity point of view among respondents whose mother is either a high school or university graduate and working has been found significantly higher. 52.1% of the participants stated that they knew “The Law of Protection of Family and Prevention of Violence against Women”. Conclusion: In this study, which was conducted with the students of the Faculty of Law, the rate of opinions defending social equality is high due to the high proportion of female students agreeing with the equitable approaches.